Alive, Kicking – and Kicking Back: Russia's Golden Mask Festival 2015. (9th July 2015) - Shevtsova, Maria
<x content-type="archive" xml:space="preserve">Abstract</x> The Golden Mask and National Theatre Award and Festival, founded in Moscow in 1994, has showcased some of the most exciting theatre to be found across Russia's vast territories: 'theatre' including opera, ballet, contemporary dance, puppetry, and newer forms that have taken root with changing artistic practices. Maria Shevtsova's brief overview of the 2015 Russian Case, a selection for foreign producers and critics, prominently features 'new drama', not least because of the difficulties recently imposed on Teatr.doc, a founding player within this powerful movement. Major young directors appear here, with crossover to their work as represented in past editions of the Russian Case, and with reference to current socio-political factors. Reviews of earlier festivals appeared in NTQ 85, 95, and 103. Maria Shevtsova, Professor at Goldsmiths, University of London, is co-editor of New Theatre Quarterly. Her most recent book is the co-authored Cambridge Introduction to Theatre Directing (2013). Her seminal Dodin and the Maly Drama Theatre: Process to Performance (2004) has been translated into Romanian, Korean, and Mandarin and, in 2014, Russian.